China's New Confucianism : Politics and Everyday Life in a Changing Society (New in Paper). - Bell, Daniel A. (Princeton University Press, 2010)
What is it like to be a Westerner teaching political philosophy in an officially Marxist state? Why do Chinese sex workers sing karaoke with their customers? And why do some Communist Party cadres get promoted if they care for their elderly parents? In this entertaining and illuminating book, one of the few Westerners to teach at a Chinese university draws on his personal experiences to paint an unexpected portrait of a society undergoing faster and more sweeping changes than anywhere else on earth. With a storyteller's eye for detail, Daniel Bell observes the rituals, routines, and tensions o.